If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x-1/3=29/3
We move all terms to the left:
-4x-1/3-(29/3)=0
We add all the numbers together, and all the variables
-4x-1/3-(+29/3)=0
We get rid of parentheses
-4x-1/3-29/3=0
We multiply all the terms by the denominator
-4x*3-1-29=0
We add all the numbers together, and all the variables
-4x*3-30=0
Wy multiply elements
-12x-30=0
We move all terms containing x to the left, all other terms to the right
-12x=30
x=30/-12
x=-2+1/2
| 36=3(3k-3) | | 2(x+7)+2=7x+2x+5 | | 1-5r+4=10 | | -132=12n | | 44x+70=77 | | 7a^2-14a=0 | | M-4m+2m=m | | 106+y=180 | | 10x+1/12=17/24 | | 9x-5+1x=10x+36 | | 1+3a+4a=8 | | -576=24t | | 3x-2.1=-4.3 | | -3(3k+2)-2=-35 | | 85=x+55+50 | | 12=2w/9 | | -19y=-342 | | 2-4(3x+8)=5 | | -33=3(-3p-2) | | 21x+4=12x+8 | | 3p-8.5=15.5 | | 21x+4=12+8 | | -3(x+2)=2(x+7) | | 17m-18=-101 | | -t/3+1=3 | | 10p+72.5=142.5 | | X-8+x=4 | | -3(3-3m)=36 | | 8-9x+10=15x-9+3x | | 5n-13=112 | | 38x+52x-67=113 | | 2x+3=0.5x-1 |